Picture description to promote improvement of speaking skill in students of second course at Salinas siglo xxi high school, Jose Luis Tamayo, Salinas. school year 2015 – 2016. - De La Cruz Del Pezo, Andrea (2016)
The topic of this project is picture description to promote improvement of speaking skill in students of second course at Salinas Siglo xxi high school, Jose Luis Tamayo, Salinas. School year 2015 – 2016. speaking skill is considered the most relevant skill to communicate with foreign people around the world; however, it is the ability that most students hardly develop. for these reasons, this project was created with the purpose of analyzing and acquiring information about the strategies and didactic material that teachers usually use to promote the speaking skill and achieve a higher level of english language in students. this research was developed with students of second course and English teachers at salinas siglo xxi high school. the methodology applied for collecting data was throughout surveys directed to students and english teachers. It was also necessary to interview some specialist professors at peninsula of Santa Elena state university. The main problem observed in this high school was the lack of opportunities that students have to develop their speaking skill; as a consequence, the students can´t communicate or share information with others using the english language. to provide a solution to this difficulty, it was indispensable to research information from books, websites, articles, and others about strategies and didactic material that help to increase the speaking skill. Taking into consideration the data collected, a good strategy to get students motivated to develop their speaking skill is to implement pictures as a didactic material to practice fun activities in class. Picture description provides a great strategy where students not only promote their ability of speaking in english at the moment they describe the pictures, they also increase their imagination, thinking and acquiring information about things that they can´t know by themselves. Finally, the results of this research have been used to design a didactic guide with fun activities of picture description to promote improvement of speaking skill.